Cascade separation of powders - Barsky, Eugene, 1974- (Cambridge International Science Pub., 2006)
The authors describe the theoretical work and practical results obtained in recent years in the area of classification of powders in moving flows. The promising nature of the cascade classification method is stressed. Mathematical models of regular, combined and irregular cascades are described. Mathematical fundamentals of the structural, dynamic and kinetics models of the process are presented. A new approach to optimising the classification processes, based on the classification curves and information theory, is explained.